Anti-proliferative activities of flavone–estradiol Stille-coupling adducts and of indanone-based compounds obtained by SnCl4/Zn-catalysed McMurry cross-coupling reactions. Issue 101 (1st October 2015) - Pathe, Gulab Khushalrao; Konduru, Naveen K.; Parveen, Iram; Ahmed, Naseem
Abstract : Flavone–estradiol adducts and indanophen based tamoxifen analogs are synthesized using SnCl4 –Zn reagent via McMurry reaction and evaluated in human cervical (HeLa) and breast cancer cells (MCF-7 and MDA-MB-231) for the anti-proliferative activity. Abstract : We described the synthesis of flavone–estradiol adducts and indanophen based tamoxifen analogs using a novel SnCl4 –Zn reagent via a McMurry cross-coupling reaction and their anti-proliferative evaluation against human cervical cancer cell lines (HeLa) and human breast cancer cell lines (MCF-7 and MDA-MB-231). A library of 32 tamoxifen analogs was synthesized using indanone and propiophenone derivatives and evaluated for anti-proliferative activities. Among them, compounds3ac, 3ad, 3ae and3ao exhibited better anti-proliferative potencies (IC50 2.13–3.81 μM) than the drug doxorubicin (IC50 < 28 μM). The flavones–estradiol adducts6ab and6ad exhibited good anti-proliferative activity (IC50 2.85 ± 0.17 μM and 2.42 ± 0.23 μM; 3.64 ± 0.28 μM and 2.93 ± 0.14 μM) against breast cancer cells (MCF-7 and MDA-MB-231) respectively and IC50 2.17 ± 0.18 μM and 2.56 ± 0.32 μM against cervical cancer cells (HeLa) respectively than the standard drug. However, compounds6ac, 6ae, 6af and6ag showed moderate activity (IC50 < 10 μM). The structure–activity relationship analysis revealed that the optimal combination of side chains at the para -position of propiophenone and fluoro substituent on the indanone moiety enhanced the anti-proliferative activities of tamoxifen analogs.